Ogólne dyrektywy wymiaru kary za wykroczenia - Kania, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This study focuses on the issue of general directives of the sentencing for infractions. In that regard, the study not only makes a reference to the statutory wording of the said regulations but also draws attention to the traditional interpretative controversies related to that issue. Furthermore, the article presents that view that although translating prescriptive provisions into practice is not an easy task, the existence of the said regulations prevents the adjudicating body from crossing the borders of discretion.
Keywords: wykroczenie; wyrok sądowy; dyrektywy o skazaniu za wykroczenie